Biodegradable Plastics Functional Groups Methyl Acrylate and Pati Garut Relationship Against Mechanical Properties - S J Iswarin; Lailatin Nuriyah; A I Sriwilujeng (Natural B, Journal of Health and Environmental Sciences, 2013)
In order to addressing the problem of plastic waste accumulating, we made biodegradable plastic from starch with methyl acrylate as initiator. The biodegradable plastics are made by grafting method on a variety of arrowroot starch composition and methyl acrylate. Variations in the composition of arrowroot starch and methyl acrylate used was 30:70; 35:65; 40:60; 45:55; and 50:50.Results of the mechanical tests e.g. tensile strength and percent elongation on plastics, show that the best value is obtained on the composition of 30:70. It reaches of (14.8 ± 2.8) MPa in tensile strength, and (5.33 ± 0.08) % in elongation percent. This value is in accordance with the results of FTIR analysis.  In here, the value of tensile strength is consistence with the value of absorbance of methyl acrylate, which indicates the concentration of functional groups C-C or the number of functional groups that formed. The greater of the concentration will be the greater of the tensile strength, while the percent elongation values are influenced by the number of functional groups C-O-C formed by arrow root starch.